Development of Heavy Equipment Rental System Using eXtreme Programming Method - Johanes Fernandes Andry (Universitas Multimedia Nusantara, 2019)
Many system development consultants nowadays using the XP framework (eXtreme Programming) in software development, This is based on the needs of the era where software can be completed quickly and when user software development is involved. The XP framework does not need too many team members, so it emphasizes effectiveness of work. In software development must begin with good planning to avoid patchwork (software crisis) in software development. The stage in research on the development of rental heavy equipment applications with an XP framework start from planning, designing, coding, testing and releasing software. Studies that do in this research include: literature studies, interviews, observations, document examinations. Next is do the analysis on the application made, and make documentation for system development. That was done as a system analysis and system design in the research. The selection of the right framework at the time of application development is very important, so that the application can be completed on time. The XP framework focuses more on making programs, the system design is enough with the CRC (Class Responsibility Collaborator). In the framework of XP, it always involves users during application development. Each module made by programmers that always tested by the system test section, so the applications that are made can be completed on time, suitable with user needs, and have high quality.